Essential Oil Composition of Salvia heldreichiana Boiss. Ex Bentham Described Endemic Species from Turkey - BASALMA, D.; GURBUZ, B.; SARIHAN, E.O.; IPEK, A.; ARSLAN, N.; DURAN, A.; KENDIR, H. (Asian Journal of Chemistry, 2010)
Plant material of Salvia heldrichiana Boiss. Ex Bentham was collected from the locality: C4 12th km on Konya, Hadim-Kizilkaya-Karaman road. Aerial parts of plants was dried in shadow then the leaves were separated from the stems. The essential oil was extracted from the leaves by hydro distillation method. The average content of essential oil was obtained as 0.22 %. The water-distilled essential oil from dried leaves of this species was analyzed by GC-MS. Total 60 components, representing 92.7 % of the oil, were characterized. The main component of essential oil was α-pinene with 13.35%. The other important compounds were identified such as spathulenol, caryophyllene oxide, α-cadinol, linalool and α-terpineol.